Detection of enteroviruses in cell cultures by using in situ transcription. - Carstens, J M (1992)
In situ transcription (IST) was shown to be useful for the detection of human enteroviral RNA in cultured cells. A primer to detect a wide variety of enteroviral genomes and a coxsackievirus type B3 genome-specific primer were demonstrated to be efficient in IST assays. Transcription times greater than 10 to 30 min did not significantly improve the acquisition of a specific signal, whereas the signal-to-noise ratio decreased with time. Inclusion of actinomycin D to suppress DNA-dependent DNA polymerase activity in reverse transcriptase decreased the signal that was obtained without improving the signal-to-noise ratio. Use of RNase H-free murine leukemia virus reverse transcriptase in the IST reaction increased the signal versus that obtained by use of the avian myeloblastosis virus enzyme, which contains endogenous RNase H activity. Exogenous RNase H added to the transcription reaction ablated the signal. Background transcription because of poorly hybridized (mismatched) primers was reduced after primer hybridization and prior to the transcription reaction by rinsing fixed cells with 3 M tetramethylammonium chloride at temperatures which dissociate mismatched primer-template duplexes. The rapid detection time and the simplicity of application suggest that IST can be performed with a high specificity for the detection of enteroviral genomic sequences in cultured cells and may be more useful than in situ hybridization for the detection of enteroviral genomes.